Da’wah, Islamic Political Thought, and Governance Transformation in the Muslim World: Mapping the Intellectual Landscape - Choirin, Muhammad; Mukti, Takdir Ali; Alfarisi, Usman (Journal of Islamic World and Politics, 2026)
This study discusses how Islamic da'wah intersects with political thought and governance. Previous studies have not addressed Islamic political ethics or specific movements, and few have systematically mapped the broader intellectual landscape. This study used a bibliometric approach based on 134 Scopus-indexed publications from 2010 to 2024, complemented by qualitative content analysis, to identify thematic trends and conceptual frameworks. The findings indicated that da'wah functions not only as a spiritual mission but also as a medium for political ethics, the realization of high-quality public policies, public mobilization, and the integration of Islamic principles into governance. This study concluded that da'wah functions not only as a spiritual mission but also as a discursive and transformative force that influences models of governance, political participation, and public awareness in the Muslim world.